2012
DOI: 10.1016/j.ultsonch.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication – A complementary ‘green chemistry’ tool to biocatalysis: A laboratory-scale study of lycopene extraction

Abstract: Lycopene is bequeathed with multiple bio-protective roles, primarily attributed to its unique molecular structure. The concomitant exploitation of two of the green chemistry tools viz., sonication and biocatalysis is reported here for the laboratory scale extraction of lycopene from tomato peel. The coupled system improved the extraction by 662%, 225% and 150% times over the unaided, only cellulase 'Onozuka R-10' treated and only sonication treated samples respectively. The sonication parameters (duration, cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Only cellulase treatment resulted in an increment of about 225% of lycopene (260 mg/g) over the untreated sample. 5% (w/w) of the biocatalyst and an incubation period of 20 min were found optimal for maximal lycopene extraction from the samples [205]. This method works in accordance with green chemistry as it does not involve the use of organic solvents for the extraction of lycopene.…”
Section: Lycopene Extraction Without Solventmentioning
confidence: 87%
“…Only cellulase treatment resulted in an increment of about 225% of lycopene (260 mg/g) over the untreated sample. 5% (w/w) of the biocatalyst and an incubation period of 20 min were found optimal for maximal lycopene extraction from the samples [205]. This method works in accordance with green chemistry as it does not involve the use of organic solvents for the extraction of lycopene.…”
Section: Lycopene Extraction Without Solventmentioning
confidence: 87%
“…Microwaves are electromagnetic waves in the frequency range 0.3 to 300 GHz, which can penetrate into certain materials and interact with the polar components to generate heat. Microwave energy acts The simultaneous application of two of the green chemistry tools, namely sonication and biocatalysis, is also reported to improve extraction of lycopene from tomato peel (Konwarh et al, 2012). In this case an significant increment in the enzyme (cellulase 'Onozuka R-10')-mediated extraction of lycopene was recorded.…”
Section: Ultrasound/microwave Assisted Extractionmentioning
confidence: 94%
“…Lycopene and its oxidation products are present in human milk and other body fluids. Human seminal plasma also contains lycopene and its levels were found to be lower in immunoinfertile men compared to normal individuals (Rao et al, 2006 13 In addition to being a powerful antioxidant, lycopene is thought to possess some other important biological properties, including induction of apoptosis, inhibition of cell proliferation and increase in gap-junctional communication (Konwarh et al, 2012 ;Rao et al, 2006), which are constantly vouching for its inclusion in functional foods and nutraceuticals.…”
Section: Many Biological and Lifestyle Factors Influence The Absorptimentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that initial enzymatic pretreatment of tomato peels followed by surfactant-assisted extraction resulted in extraction yields ten times as high as those of untreated peels (PAPAIOANNOU & KARABELAS, 2012). Enzyme pretreatment was effi ciently combined with sonication and SC-CO 2 extraction for tomato lycopene recovery (KONWARH et al, 2012;LENUCCI et al, 2015). A thorough knowledge of enzymes, their mode of action, and the conditions for their optimum activity, together with selection of the right types of enzymes, are essential for their effi cient usage for extraction purposes (SOWBHAGYA & CHITA, 2010).…”
mentioning
confidence: 99%